What you have to do is solve for two possible equations. They are

3x + 6 = 9

and

-(3x + 6) = 9 which is the same as

-3x - 6 = 9

So you must solve both:

3x + 6 = 9

3x = 3

**x = 1**

-3x - 6 = 9

-3x = 15

**x = -5**

**So the answer for this is x = -5,1**

It is given that |3x+6|=9

As the absolute value of 3x + 6 is equal to 9 either 3x + 6 = 9 or -(3x + 6) = 9

3x + 6 = 9

=> 3x = 3

=> x = 1

-(3x + 6) = 9

=> 3x + 6 = -9

=> 3x = -15

=> x = -5

**The solutions of x are x = 1 and x = -5**

| 3x + 6 | = 9

To solve this use the equations

3x + 6 = 9 and. 3x + 6 = -9 now subtract 6 on both side of both equation

By subtracting, you should get

3x = 3 and 3x = -15 now divide both sides of both equation by 3

By dividing, you should get

x = 1 and x = -5 which are your answers

We recall that the absolute value means:

|p| = a>0

We'll have to solve 2 cases:

1) 3x+6 = 9

We'll subtract 6 both sides:

3x = 9 - 6

3x = 3

We'll divide by 3:

x = 1

2) 3x+6 = -9

We'll subtract 6 both sides, to isolate x to the left side:

3x = -6 - 9

3x = -15

We'll divide by 3:

x = -5

**The equation has 2 solutions : {-5 ; 1}.**